Mn(III)-induced reaction of 1,1-diarylethenes with potassium thiocyanate: a novel synthesis of dithiocyanates - Ha, Nguyen Van; Bao Quyen, Tran Thi (Vietnam Journal of Chemistry, 2016)
Reactions of 1,1-diarylethenes with potassium thiocyanate in the presence of manganese triacetate dihydrate was uncovered to be a simple approach to dithiocyanates. This new method was applied to synthesize some new 1,2-dithiocyanatoethane derivatives. High yields and unbelievable short reaction time as well as simple procedure made this synthetic method become a practical alternative to reported ones